Determining the Mechanism for Low Sludge Yields in the Cannibal Solids Reduction System: Van Ginkel et al. (1st January 2018) - Van Ginkel, Steven W.; Miceli, Joseph; Kim, Bi‐o; Yang, Ziming; Young, Michelle; Marcus, Andrew; Rittmann, Bruce E.
ABSTRACT: : Extracellular polymeric substances (EPS) and solids concentrations in samples from the Interchange Bioreactor (IBR), and return activated sludge (RAS) from Cannibal facilities having low and high sludge yields, were analyzed to understand the mechanisms behind low sludge production. Low sludge yields correlated to more EPS degradation, higher concentrations of iron, and reducing conditions in the IBR. In the low yield facilities, iron was reduced when the RAS passed through the anaerobic and reducing conditions of the IBR, and this led to more EPS solubilization and degradation. This "futile cycle" of EPS production and degradation appears to may have been most responsible for reducing sludge yields.